Advanced Practice Registered Nurse Onboarding and Orientation Program - Lambert, Cheryl (Journal Of Nursing Practice, 2020)
Background: The influx of advanced practice nurses into the healthcare industry has established the need for a postgraduate program for APRNs. Numerous studies have shown the efficacy of an onboarding process; however, there were limitations to the reviews.Purpose: This study aimed to determine formal orientation and orientation programs, compared to current APRN orientation and orientation can improve the competence and quality of APRN care for eight weeks.Methods: The participants were six currently practicing APRNs with eleven months to five years practicing as independent providers. The response rate in the pre-assessment phase was 100% and 66.7% in the post-assessment phase. Two APRNs came onboard after the start of the project, and one APRN opted out. There were no preceptors available for the completion of the CoEPCE competency tool. The APRN onboarding and orientation program utilized a competency tool with pre- and post-assessments. Emails with attached competency tool sent to APRNs for completion of pre- and post-assessments. The APRNs completed the pre- and post-competency assessments on the first day of implementation and the last day of week eight. The collection of data from the pre- and post-competency tool commenced in week nine and imported into Microsoft Excel for analysis. The data collected from the CoEPCE tool, as highlighted in the implementation phase, has significant changesResults: The outcomes revealed that the changes were not significantly statistical at the p-level of 0.05 in the seven domains because none of the p-values were less than 0.05. However, the results revealed that deficits in statistical significance should not deem that the onboarding process was not successful.Conclusion: The results demonstrated evidence of the importance of an APRN postgraduate program in enhancing competencies. However, larger sample sizes are substantial to show statistically changes for reliability and validity